Perfectionism and Self-Esteem in Students: An Integrative Systematic Analysis - Nursunja, Dera; Polla, Rina Ruth (Indonesian Scientific Publication, 2025)
Students face various academic demands that can significantly affect their psychological well-being. Self-esteem plays a crucial and influential role in determining how students respond and adapt to these pressures, while perfectionism often emerges as a behavioral response to low self-esteem. This research aims to comprehensively examine the relationship between self-esteem and perfectionism among students through a systematic literature review, involving 50 articles which were then filtered down to 15 articles deemed most relevant to the topic under investigation, and subsequently included as 6 journal articles focused on the relationship between self-esteem and perfectionism, specifically targeting the student population as the main subjects, with sources obtained from Google Scholar and ResearchGate. The findings of the review indicate that maladaptive perfectionism has a significant negative correlation with self-esteem, meaning that the higher the maladaptive perfectionism, the lower the self-esteem of students, while adaptive perfectionism shows varying results, namely that adaptive perfectionism has a positive relationship with self-esteem, which means that the higher the adaptive perfectionism, the higher the self-esteem of the individual; however, other studies have found that adaptive perfectionism can also lower self-esteem. Several studies also reveal that self-esteem can act as a mediator in the relationship between perfectionism and depression. These findings highlight the importance of strengthening students' self-esteem to prevent the negative impact of perfectionism on mental health.